(untitled) (Universal International Scientific Journal, 2026)
This article discusses the effectiveness of using modern pedagogical technologies in teaching the microscopic structure of the pancreas, one of the important sections of histology. The role of interactive methods, problem-based learning and information technologies in strengthening students’ theoretical knowledge, developing practical skills and increasing didactic competence is analyzed. The results of the study show that classes organized on the basis of pedagogical technologies significantly increase the level of knowledge and independent thinking of students.